2009
DOI: 10.4067/s0717-65382009000100012
|View full text |Cite
|
Sign up to set email alerts
|

Distribucion, Batimetria Y Alimentacion De Epigonus Crassicaudus De Buen, 1959 (Perciformes: Epigonidae) en La Costa De Chile

Abstract: By mans of the fisheries activity records and the information of tralws sampling carried out in surveys of common hake the batimetric and latitudinal distributions of cardinal fish (Epigonus crassicaudus) in the Chilean coast were studied. Aditionality, information on feeding habits of cardinal fish through analysis of the gastric content on samples collected in the central zone from Chile are reported. According to fishery data the cardinal fish would concentrate their distribution between Valparaíso (33º04'S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
(6 reference statements)
0
11
0
1
Order By: Relevance
“…Larger fish individuals inhabit deeper waters, which is known as the bigger‐deeper phenomenon (Haedrich & Rove, 1977; Pollini et al ., 1979), in which adults benefit from reduced metabolic rates and increased life probabilities owing to low temperatures in deeper waters (Cushing, 1982; Love, 1970, 1980). In general, a large number of deep‐sea fishes carry out diel vertical migrations between pelagic and benthic realms (Abramov & Lipskaya, 1989), which may be related to the feeding migratory habits in the water column (Leal et al ., 2009). For example, the diet of a similar species, E. spinax , on the upper continental slope off the Algarve (southern Portugal) suggests a fairly generalized benthopelagic foraging behaviour primarily tuned to pelagic macroplankton/microneckton, teleost fish and cephalopods (Neiva et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Larger fish individuals inhabit deeper waters, which is known as the bigger‐deeper phenomenon (Haedrich & Rove, 1977; Pollini et al ., 1979), in which adults benefit from reduced metabolic rates and increased life probabilities owing to low temperatures in deeper waters (Cushing, 1982; Love, 1970, 1980). In general, a large number of deep‐sea fishes carry out diel vertical migrations between pelagic and benthic realms (Abramov & Lipskaya, 1989), which may be related to the feeding migratory habits in the water column (Leal et al ., 2009). For example, the diet of a similar species, E. spinax , on the upper continental slope off the Algarve (southern Portugal) suggests a fairly generalized benthopelagic foraging behaviour primarily tuned to pelagic macroplankton/microneckton, teleost fish and cephalopods (Neiva et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…El besugo Epigonus crassicaudus de Buen, 1959 es un pez caracterizado por hábitos mesobento/pelágicos cuyos individuos adultos habitan el talud continental y montes submarinos donde forman densas agregaciones, mientras que los juveniles se encuentran desagregados en la zona pelágica cercana a la plataforma continental (Parin 1987). El besugo es una especie endémica de las costas frente a Chile y de acuerdo con la información pesquera, las mayores abundancias se encuentra distribuidas entre los 29°00'S y 42º50'S (Leal et al 2009) entre los 200 y 400 m de profundidad (Wiff et al 2008).…”
Section: Introductionunclassified
“…The cardinalfish (Epigonus crassicaudus) (De Buen, 1959) belongs to the Epigonidae family, a poorly studied group of perciform fishes, with permanent records of new species . This species is endemic along the Chilean coast, distributed mainly between 29°00'S and 42°50'S, in depths between 100 and 500 m (Wiff et al, 2005;Leal et al, 2009). Cardinalfish landings ha-_____________________ Corresponding editor: Alejandra Volpedo ve been recorded since 1992 with 579 t at that year, its peak in landings was 5,792 t recorded in 2000 (SERNAPESCA, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding its biology, some studies addressing the food and trophic levels of this species have been reported (e.g., Arancibia & Meléndez, 1987;Neira & Arancibia, 2004;Leal et al, 2009;Sepúlveda et al, 2018). Also, the annual reproductive cycle and maturity in length to females was reported by Flores et al (2015).…”
Section: Introductionmentioning
confidence: 99%